Activist Leaders of San José : En sus propias voces - Mendez-Negrete, Josie (Book collections on Project MUSE., 2020)
"Challenging stereotypes, this book unearths and makes visible lived experiences of Chicana/Latino activists from San Jose, California, who made contributions to the cultural and civic life of the city. Through oral histories, we see a portrait of grassroots leadership in the twentieth century"--